Facebook in Higher Education: Exploring the educational use of Facebook by undergraduate students - Lee, Cheng Ean Catherine *; Teh, Phoey Lee * (2015)
The learning environments in higher education are moving towards the integration of information and communication technology (ICT) such as Web 2.0 and social media. Recent years have witnessed an increased interest of using social media in higher education and this has created a growing phenomenon for the educational use of social networking sites such as Facebook, to create, engage, and share existing or newly produced information among the students. The prevalence of social media in higher education has attracted the attention of researchers who have sought to understand the use of social media for learning and educational. Besides, many higher education institutions have begun to incorporate variety of digital technologies for teaching and learning, while educators are finding themselves expected to catch up with the world of social media applications and social media users. The educators are seeking the potential of social networking sites for engaging the students in their studies as well as to make the classes more interactive, and to achieve student learning outcomes. With this in mind, this paper presents a qualitative analysis of the Facebook closed group activities of undergraduate students in a Malaysian private university. The analysis of data will -related use of Facebook closed group and issues relating to student use of Facebook for educational purposes due to its increasing prevalence in the everyday lives of students. Finally, this paper will provides useful insights for academics interested in using social networking sites for teaching and learning and for researchers interested in pursuing social media in higher education research.